Ritual Herb Pill Induced Myopathy in a Hypercholesterolemic Patient Treated with Simvastatin - Wiwanitkit, Viroj (Journal of Basic and Applied Pharmacology, 2015)
A case of female patient with myopathy associated with simvastatin administration is reported. She revealed no history of drug use but only ritual herb ball pill. The patient also did not do any severe exercise. Elevation of serum CK exceeding three times the upper limit, was observed in this patient and returned to normal limits within 2 weeks after simvastatin administration was canceled. This is the first probable case report of myopathy side effect from concomitant use of ritual herb pill to simvastatin administration in Thai patient.